High refractive index sensing highly sensitive and low loss SPR sensor based on hollow-core D-shaped optical fiber - Kumar H.; Ramani U.; Kumar R.; Singh B.K.; Pandey P.C. (My University, 2025)
A hollow-core D-shaped optical fiber-based surface plasmon resonance (SPR) sensor for low-loss and highly sensitive liquid analytes detection is theoretically investigated. The gold (Au) metal nanolayer is coated on the cladding etched D-shaped °at surface to develop the plasmonic e®ect. The nanolayer coating on the outer °at surface is very easy compared to the inside hollow-core, so our hollow-core sensor manufacturing is too easy compared to other hollow-core refractive indices (RIs) detection sensors. The resonance e®ect between analytes filled fundamental guided core mode and surface plasmon polariton mode of the D-shaped hollow-core optical fiber sensor is used to obtain the detections of analytes RIs variations. We have found good linear results (R2 > 0:99) in analytes RIs versus resonance wavelength for gold layers thicknesses for the analytes RIs range of 1.45–1.52. This hollow-core D-shaped optical fiber sensor achieves the maximum wavelength sensitivity of 23500 nm RIU-1 and a corresponding resolution of 4:26 × 10-6 RIU. We have obtained the maximum figure of merit (FOM) of 228 1/RIU. The proposed sensor may be highly active in detecting the biological and chemical liquid analytes. © World Scientific Publishing Company.